Levels of Mathematical Argumentation: An Analysis of Junior High School Students’ Reasoning in Number Pattern Tasks - Marlina Marlina; Rohati Rohati; Sri Winarni; Ade Kumalasari (Journal of General Education and Humanities, 2026)
Mathematical argumentation is important for developing students’ reasoning abilities. This study aims to analyze junior high school students’ written and oral argumentation abilities when solving reasoning tasks. This research employed a descriptive qualitative approach, involving 31 ninth-grade students from SMP Negeri 7 Muaro Jambi. The study was conducted in the odd semester of the 2024/2025 academic year. The research instruments consisted of a mathematical reasoning test, interview protocols, and documentation. The mathematical reasoning test included three questions. The results of the tests and interviews were analyzed using the main components of Toulmin’s argumentation model, which consist of claims, data, warrants, backing, qualifiers, and rebuttals. Based on the test and interview results, students’ argumentation abilities were categorized into five levels, from Level 1 to Level 5. The findings show that 31 students (100%) reached Level 1, 15 (48.38%) reached Level 2, and 9 (29.03%) reached Level 3. No students reached Level 4 or Level 5. These findings indicate that students can construct claims, data, and warrants when solving mathematical reasoning tasks. However, students still need to be trained to develop backing, qualifiers, and rebuttals in order to complete the argumentation process appropriately in both written and oral forms.